(untitled) (Revista Latino-Americana de Enfermagem, 2023)
Objective: to evaluate the occurrence of offensive behaviors at work, their characteristics and association with sex, stress, burnout and depression in health workers. Method: a cross-sectional, descriptive and quantitative study carried out with 125 workers from the Brazilian Unified Health System. The data were collected from June 2021 to April 2022 through three self-applied questionnaires that assess personal and occupational characteristics; offensive behaviors, stress and burnout; and depressive symptoms. Descriptive statistics, the chi-square association test and logistic regression analysis were applied. Results: 44% of the sample reported 83 behaviors, with threats of violence as the most frequent ones (26%). Nursing technicians/assistants, nurses and physicians were the most exposed professionals. The main aggressors were the patients, except for bullying, which was perpetrated by co-workers (48%). There was an association between offensive behaviors and burnout (OR: 4.73; 95% CI: 1.29-17.3; p=0.02) and between offensive behaviors and depression symptoms (OR: 1.05; 95% CI: 1.01-1.10; p=0.02). Conclusion: the occurrence of offensive behaviors in health work is frequent and characteristic and burnout and depressive symptoms respectively increased 4.73 and 1.05 times the chances of workers suffering these offensive behaviors in the work environment.